Net Promoters Score (NPS) And Its Relation to Other Marketing Customer Satisfaction Measures - Grzegorz BIESOK; Jolanta WYRÓD-WRÓBEL (Communications of International Proceedings, 2021)
In our paper we intended to verify the relationship between the NPS and other customer satisfaction measures commonly used in consumer research. We collected the results of 10 customer satisfaction surveys, we harmonized and combined all the data and used a simulation with the bootstrap method to generate two sets of subsamples. For each subsample we calculated the NPS and other customer satisfaction measures. Next, we examined how these measures correlate with each other. Then we were changing the trichotomy of the NPS scale and observing changes in correlation of new-formula NPS and other satisfaction measures. In our simulations, we achieved better compliance with the other satisfaction indices when the NPS score-classes was set as: Detractors (0-3) Passives (4-7) Promoters (8-10). Therefore we proposed a modification of the NPS indicator for the purposes of customer satisfaction surveys.
Keywords: consumer research; customer satisfaction; customer satisfaction measurement; Net Promoters Score (NPS).